Ketidaksesuaian Antara Pencatatan Persediaan dan Fisik Stok Sebagai Temuan dalam Management Letter pada Perusahaan X (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the discrepancy between inventory records and physical stock as a key audit finding noted in the management letter at Company X. Such discrepancies affect the reliability of financial reporting and the effectiveness of internal controls. The study employs a descriptive qualitative approach with data collection techniques including interviews, direct observation, and documentation. The findings reveal that the inventory recording system at Company X faces several challenges, such as delayed recording, lack of documentation for damaged goods, and reliance on manual input that is prone to human error. In addition, the stock opname procedure is conducted only annually and is not fully implemented in accordance with the established SOP. The discrepancy between inventory records and physical stock has a direct implication in audit findings, which are noted in the management letter as internal control weaknesses. The study recommends improvements in the recording system, regular stock opname implementation, staff training, and the application of barcode technology to enhance inventory data accuracy.